Utilizing environmental DNA metabarcoding and local ecological knowledge for fish biodiversity assessment in Rivers of Java, Indonesia - Kurniawan Kurniawan; Wibowo Arif; Prakoso Vitas Atmadi; Chadijah Andi; Astuti Septiana Sri; Pratama Boby Bagja; Nafiqoh Nunak; Haryono Haryono; Dahruddin Hadi; Surbani Indah Lestari; Jaya Yohanes Yudha P.; Sudarsono Sudarsono; et al. (Knowledge and Management of Aquatic Ecosystems)
Knowledge of fish biodiversity in aquatic ecosystems is critical for sustainable management and conservation of inland waters. Indonesia highlights these issues with its rich natural aquatic biodiversity, which is seriously threatened by human development. To inform restoration goals, we examined the fisheries biodiversity in eight coastal rivers in Java (Indonesia) using environmental DNA (eDNA) and local ecological knowledge (LEK). Three replicate 1L water samples were collected and filtered from each river for environmental DNA metabarcoding, targeting the 12S rRNA gene. LEK surveys were conducted with 50 indigenous residents near the eight focal rivers, including fishers, anglers, traders, and farmers. The combined methodology identified a total of 51 fish species, including 32 through eDNA and 30 through LEK surveys. Both methods detected the same eleven species (22%) in total. The eDNA technique revealed 21 species that fishers had not reported, while fishers reported 18 species that eDNA did not detect. The eDNA approach improves biodiversity identification and monitoring, including the detection of aquatic species that are not recorded by fishermen, especially where historical quantitative data are fragmentary. Meanwhile, LEK can supplement eDNA findings by identifying species that eDNA alone may not detect. We recommend this combined approach where traditional fisheries assessments using capture-based techniques are impractical or cost-prohibitive. Our findings highlight its value in guiding adaptive management strategies in resource-limited regions where traditional fisheries assessments are impractical. Enabling targeted conservation efforts helps protect ecologically significant and culturally important species within priority habitats.